The multifaceted nature of IL-10: regulation, role in immunological homeostasis and its relevance to cancer, COVID-19 and post-COVID conditions - Carlini, Valentina; Noonan, Douglas M.; Abdalalem, Eslam; Goletti, Delia; Sansone, Clementina; Calabrone, Luana; Albini, Adriana (Frontiers in Immunology, 2023)
Interleukin (IL)-10 is a pleiotropic cytokine that has a fundamental role in modulating inflammation and in maintaining cell homeostasis. It primarily acts as an anti-inflammatory cytokine, protecting the body from an uncontrolled immune response, mostly through the Jak1/Tyk2 and STAT3 signaling pathway. On the other hand, IL-10 can also have immunostimulating functions under certain conditions. Given the pivotal role of IL-10 in immune modulation, this cytokine could have relevant implications in pathologies characterized by hyperinflammatory state, such as cancer, or infectious diseases as in the case of COVID-19 and Post-COVID-19 syndrome. Recent evidence proposed IL-10 as a predictor of severity and mortality for patients with acute or post-acute SARS-CoV-2 infection. In this context, IL-10 can act as an endogenous danger signal, released by tissues undergoing damage in an attempt to protect the organism from harmful hyperinflammation. Pharmacological strategies aimed to potentiate or restore IL-10 immunomodulatory action may represent novel promising avenues to counteract cytokine storm arising from hyperinflammation and effectively mitigate severe complications. Natural bioactive compounds, derived from terrestrial or marine photosynthetic organisms and able to increase IL-10 expression, could represent a useful prevention strategy to curb inflammation through IL-10 elevation and will be discussed here. However, the multifaceted nature of IL-10 has to be taken into account in the attempts to modulate its levels.